Low-power current reference with temperature compensation by subthreshold leakage current. (March 2021) - Xu, Zhentao; Lin, Zhi
Abstract: A compact and power-efficient current reference with curvature-correction temperature characteristics is presented. Introducing of PTAT current into the loop of CTAT current generator results in reduced TC of VGS, which makes the aspect ratios of MOSFETs decrease when perform the first-order temperature compensation. Application of the subthreshold leakage current with curvature temperature feature to the reference current improves the temperature stability of output current to 52.1 ​ppm/°C over temperature range of −30 to 120 ​°C. This reference implemented in a 180 ​nm process with core area of 0.08 ​mm 2 can work in a wide voltage range from 1.0 ​V to 2.4 ​V and consume current about 1 ​μA ​at 1.2 ​V.